Foulkes and Intersubjectivity: A Pioneer in Uncharted Territories. (September 2014) - Potthoff, Peter
Since the 1940s Foulkes developed his theory of group analysis. Originating from Freudian psychoanalysis, Foulkes—through his experiences with groups—developed new concepts about human motivation, pathogenesis of mental illness and therapeutic options. In contrast to drive theory, he postulated relationality, search for contact and exchange, and belongingness as central motivations. In a sometimes surprising congruence with Foulkes' ideas, the intersubjective-relational paradigm came into being during the 1980s and has since, as 'intersubjective turn', substantially influenced contemporary psychoanalytic theorizing. It could serve as a bridge between different psychoanalytic schools as well as between contemporary psychoanalysis and group analysis. Basic tenets of group analysis and relational psychoanalysis are demonstrated, differences and similarities pointed out.